(3GdQhVI GdWHjIs - (3CHhSYjO YHjOGddg Hf LHQFjd Hf YHjOGddg Hf HNJjThYs; (3GHf HNJjThY , YHjOGddg Hf LHQFjd Hf YHjOGddg, CHh SYjO,J (B453 (3g` s ((3SdGeI Hf CHj efUhQ GdefLe GdeJWHH s)
(3ChdgG (B:s
(3Gddge CYf Ydi WGYJc cd aGVd CWGd HbGA GdCSJGP SCdfi COGe Gddg JCjjOg Cf GNJUQ dg ef cJGHj GdefYhJ HJPcQI GdMGVQ hRGO GdeSGaQ s
(3BNQgG (B:s
(3agPG eG Ynf di ai LhGH eG SCd Yfg hbO ChQOJg eNJUQkG hCQLhCf jchf cGajkG dg aj ZQVg , caGfj Gddg ajg GdeMPhQ , Hefg hdWag s
(3Vef eLehY s
(3Ydi GdfSNI Jedc SfI (B720(3g`s
(3fSNI fajSI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdWHs